The Hermeneutics of Θεραπερεια (Healing) in John 9:1-12 and Its Application in the Christ Apostolic Church, Ibadan, Nigeria - Oderinde, Olatundun Abosede; Ademola, Julius Olajide (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025, 2025)
This study explores the physical, spiritual, and symbolic dimensions of healing performed by Jesus Christ as recorded in the Gospel of John. Healing occupies a central place in Jesus’ earthly ministry. In obedience to Christ’s directive to his followers to preach the gospel and heal the sick, the Christ Apostolic Church (C.A.C.) has made healing one of its core practices. The various healing methods employed by Jesus—through touch, faith, prayer, anointing with oil, distance healing, and the use of water—form the foundational principles upon which the healing ministry of the C.A.C. is built. The healing narrative in John 9 was chosen for analysis because it features the use of natural elements such as water, clay, and saliva—methods that resonate with the healing practices found within the C.A.C. However, the study observes that the healing practices of some ministers within the Church fall short of the biblical model exemplified by Jesus. The questionable character of certain healers often casts doubt on the authenticity of their ministry, leading some believers to question whether such individuals are truly called by God. Reports of immoral behavior, such as adultery, fornication, or involvement with familiar spirits, undermine the credibility of divine healing. θεραπεύω means “to heal,” “to cure,” or “to restore to health.” This study is motivated by the need to undertake an exegesis of θεραπεύω to extract healing principles from the ministry of Jesus and its application in the Christ Apostolic Church. Employing the historical-exegetical method of biblical research, the text of John 9:1–12 was examined alongside qualitative data collected through structured interviews analyzed descriptively. Findings reveal that Christ Apostolic Church upholds, to a significant extent, the principles of healing reflected in the Gospel of John. Nonetheless, the study recommends continuous improvement in aligning healing practices with biblical standards. Keywords: θεραπεύω ( therapeuo ), Health, Miracle, Salvation, Christ Apostolic Church (C.A.C.